2015
DOI: 10.17269/cjph.106.4774
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent suicidal ideation in young adults

Abstract: OBJECTIVES: Recurrent suicidal ideation (SI) may be linked to an increased risk of making suicide plans and suicide attempts. The objectives were to describe the frequency of SI recurrence in a population-based sample of young adults, and to compare mental health diagnoses, substance use, use of health services and medication use among those with and without recurrent SI.METHODS: Data were collected from 785 participants at age 20 years and again at age 24. Chi-square tests were used to compare participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…In fact, studies focusing on adolescent and young-adult populations have found that, unlike other age groups, young people have an increased risk of suicide due to depression, 12 frequent experiences of bullying, 13 belonging to marginalized groups, 14 and substance use or mood disorders. 15 Given the known spatial association of suicide rates with socioeconomic deprivation, and the fact that youth have unique risk factors for suicide which also are impacted by socioeconomic status, evaluating and understanding the spatiotemporal variance of suicide clusters can support public policies.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies focusing on adolescent and young-adult populations have found that, unlike other age groups, young people have an increased risk of suicide due to depression, 12 frequent experiences of bullying, 13 belonging to marginalized groups, 14 and substance use or mood disorders. 15 Given the known spatial association of suicide rates with socioeconomic deprivation, and the fact that youth have unique risk factors for suicide which also are impacted by socioeconomic status, evaluating and understanding the spatiotemporal variance of suicide clusters can support public policies.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide ideation refers to thoughts about killing oneself, ranging from wishing to be dead to developing a plan to kill oneself (Kessler et al, 1999;Lewinsohn, Rohde, & Seeley, 1996). Suicide ideation is prevalent among adolescents and young adults (Harkavy-Friedman, Asnis, Boeck, & DiFiore, 1987;Wilcox et al, 2010) and can be more than a transient phenomenon in that 32% of young adults with suicidal ideation report being suicide ideators 4 years later (Dugas, Low, O'Loughlin, & O'Loughlin, 2015). A large number of university students ideate about suicide, which warrants suicide ideation as a legitimate area, in and of itself, and as a concern for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly half of the study population had multiple psychiatric diagnoses, and over one-third of patients had a history of at least one prior suicide attempt. Other studies have also found frequent recurrence of suicidal ideation and attempts, with a higher likelihood in patients with concomitant substance abuse [ 22 , 23 ]. This data highlights the need for ongoing care and the potentially recurrent nature of psychiatric illness in patients with suicidal thoughts and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…These encounters only include visits to our facility and do not account for possible visits to other facilities. A previous study found that 14% of the patients with an ED visit for mental health or substance abuse had a return visit to the ED or hospitalization within 30 days, particularly for older adults [ 22 ]. Other studies have similarly reported that patients with both a psychiatric and substance abuse diagnoses had significantly higher ED utilization [ 14 , 24 26 ].…”
Section: Discussionmentioning
confidence: 99%